(untitled) (Asian Business Research, 2022)
This paper mainly analyzes the value-added mechanism in the supply chain and the experience of cold chain logistics development based on the cold chain logistics transportation of seafood in Japan. The support and protection of the law for cold chain logistics, as well as the development of the degree of informationization and the construction of infrastructure facilities are studied from the government level. On this basis, certain problems are found, for example, the lack of management level, the lack of excellent talent reserve, the backwardness of infrastructure facilities, and the low degree of information technology, etc. Some rationalization suggestions are provided for the development of seafood transportation and the development of the supporting logistics supply chain system in China.